Learning and memory - Rudmann, Darrell S. (SAGE Publications, Inc, 2017)
Learning and Memory provides an integration of theoretical perspectives, presented clearly, concisely, and with an approachable writing style, ensuring a coherent and comprehensive learning experience for the reader.